Vietnamese Higher Education Challenges: Quality Accreditation, Rankings and Ratings - Duc, Nguyen Huu; Anh, Tran Mai; Hien, Ta Thi Thu (VNU Journal of Science: Education Research; Vol 39 No 1, 2023)
A study analyzing data from an international university ranking system, a regional rating system, and quality accreditation processes revealed that challenges of Vietnamese higher education are identified in three levels: the national system, the institution level, and training programs. Analysis of the multiple datasets exposed 20 potential gaps at the educational institution and training program level assessments, which may be the reasons preventing the top five ASEAN Vietnamese higher education to further advance to higher levels. On that basis, the report proposes eight solutions to improve the quality and competitiveness of the university accreditation, ranking and rating systems.